Potencial bacteriocinogênico e probiótico de bactérias ácido láticas isoladas de leite e queijos artesanais - Hermanns, Gislaine (2013)
Among the wide range of products naturally fermented by lactic acid bacteria (LAB), there are the homemade cheeses. These bacteria are inherent to the raw milk and the fermentation process for producing compounds responsible for the flavor and texture of the products. Its use is one of the oldest food preservation techniques, since they are able to produce substances with antagonistic action against spoilage and pathogenic microorganisms, particularly Listeria monocytogenes, commonly found in refrigerated dairy products. In addition, many lactic acid bacteria have probiotic potential, thus becoming the most attractive one for its use. In North West Frontier region of Rio Grande do Sul a typical cheese is produced, popularly called colonial cheese, which its knowledge of fabrication techniques have been transferred verbally through generations. For being manufactured, in most cases, with raw milk without the addition of starter cultures and under poor conditions of hygiene, it has a diverse unwanted microbial population. This aspect is characterized as a danger to consumers, as well as spoilage organisms that can also serve as a carrier of pathogenic microorganisms. The objective of this study is to isolate and identify lactic acid bacteria with probiotic characteristics and bacteriocinogenic from milk and artisan cheeses produced in this region. Thus initially the BAL were isolated and tested for antagonist ability against pathogens, and then checked the ability to produce antimicrobial substances of proteinaceous nature (bacteriocins), as well as resistance to biological barriers, as a criteria for the selection of isolated with probiotic potential. Molecular identification was performed by obtaining and sequencing of 16S rDNA or the ITS region. Subsequently, the isolated were evaluated for antimicrobial resistance of clinical use and the production of the enzyme β-hemolysin as virulence factors. The selected isolated were used as inoculum in cheese produced at a pilot level, with monitoring of physical-chemical and microbiological, over twenty-eight days of maturation under refrigeration. Of total lactic acid bacteria isolated twentyone (34.43%) showed antagonistic potential against pathogenic microorganisms reference. Of these, seven (33.33%) were able to produce antimicrobial substances of nature protein, being classified as possibly bacteriocinogenic and five (23.81%) isolated were shown to possess probiotic potential. The molecular identification of these proved to treat Enterococcus durans, Enterococcus faecium and Lactobacillus plantarum. The isolated F9 and U5 were selected and added as bacteriocin and probiotic culture, respectively, as a pilot project in cheese artificially contaminated with Listeria monocytogenes. No isolated was able to remove this pathogenic organism in the cheese, and the cultivation of bacteriocinogenic shown to be capable of maintaining viable cells of the microorganism stable during the maturation period. The probiotic proved to be able to withstand during the ripening of the cheese, while maintaining a viable cell number in the order of 107 - 108UFC.g-1 cheese, which allows its use with probiotic purpose.